[tex]\large\boxed{v=0}[/tex]
In this question, we're solving the equation by figuring out what v equals to.
We are solving:
[tex]-2(-3v-5)-5v=12(1+v)-2[/tex]
Solve:
[tex]-2(-3v-5)-5v=12(1+v)-2\\\\\text{Distribute the -2 to the -3v and -5}\\\\6v+10-5v=12(1+v)-2\\\\\text{Distribute the 12 to the 1 and v}\\\\6v+10-5v=12+12v-2\\\\v+10=12+12v-2\\\\\text{Subtract both sides by 12v}\\\\-11v+10=12-2\\\\\text{Subtract both sides by 10}\\\\-11v=-10+12-2\\\\-11v=2-2\\\\-11v=0\\\\\text{Divide both sides by -11}\\\\\boxed{v=0}[/tex]
When you're done solving, you should get v = 0.
This means that v = 0 would be your final answer.